A proposal to include human rights principles Arabic language curriculum - A survey- Kingdom of Saudi Arabia - Alghamdi, Ibrahim Abdulrahim (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree to which Arabic curriculum in Saudi Arabia include the most prominent principles of human rights and the nature of that inclusion, and then to build a proposed conception to include the principles of human rights appropriate to you at one of the three stages of primary, middle and secondary. The study followed the descriptive approach using the method of content analysis, and the study reached one of the most prominent findings: The inclusion of the principles of human rights in the curriculum was found to be weak in the overall range. The findings also showed that the decisions balanced somewhat between explicit and implicit rights. Each of the key fields also varied, as the first field: civil and political rights came ahead by a wide margin at the expense of other economic, social, developmental and environmental rights. Finally, the study suggested in light of its findings a vision for the development of the Arabic language curriculum in Saudi Arabia in the light of human rights.
Keywords: A Proposed Conception; Human Rights Principles; Arabic Language Curriculum; Kingdom of Saudi Arabia